Computer prediction of paratope on antithrombotic antibody 10B12 and epitope on platelet glycoprotein VI via molecular dynamics simulation. Issue 2 (December 2016) - Liu, Wenping; Liu, Guangjian; Zhou, Huiyun; Fang, Xiang; Fang, Ying; Wu, Jianhua
Abstract Background Interaction between immunoglobulin-like receptor glycoprotein VI (GPVI) and collagen plays a central role in platelet activation and sequent firm adhesion. Of various antithrombotic agents targeting GPVI, antibody 10B12 is of great potential to block the GPVI-collagen interaction, but less is known about 10B12 paratope and GPVI epitope. Methods Along the pathway in the computer strategy presented in our previous work, the 10B12/GPVI complex model was constructed through homology modeling and rigid-body docking, and the molecular dynamics (MD) simulation was used to detect the paratope residues on 10B12 and their partners on GPVI. Quantified by free and steered MD simulations, the stabilities of hydrogen bonds and salt bridges were used to rank the contributions of interface residues to binding of 10B12 and GPVI. Results We predicted 12 key and seven dispensable residues in interaction of 10B12 to GPVI with present computational procedure. Besides of the 12 key residues, two are epitope residues (LYS41 and LYS59 ) which had been identified by previous mutation experiments, and others, including four epitope residues (ARG38, SER44, ARG46 and TYR47 on GPVI) and six paratope residues (GLU1, ASP98, GLU102, ASP107, ASP108 and ASP111 on 10B12), were newly found and also might be important for the 10B12–GPVI binding. The seven predicted dispensable residues on GPVI were had been illustrated in previous mutation experiments. Conclusions The present computer strategy combining homology modeling, rigid body docking and MD simulation was illustrated to be effective in mapping paratope on antithrombotic antibody 10B12 to epitope on GPVI, and have large potential in drug discovery and antibody research.